A fuzzy multi criteria risk assessment based on decision matrix technique: A case study for aluminum industry - Gul, Muhammet; Guneri, Ali Fuat (ELSEVIER SCI LTD, 2016)
Decision matrix risk-assessment (DMRA) technique is a systematic approach widely used in the Occupational Health and Safety (OHS) risk assessment. In a typical matrix method approach, a measure of risk value is obtained by evaluating two risk factors as the likelihood of a hazard and the severity of the hazard when it arises. In this paper, a fuzzy approach enabling experts to use linguistic variables for evaluating two factors which are the parameters of matrix method is proposed to deal with shortcomings of a crisp risk score calculation and to decrease the inconsistency in decision making. The parameters likelihood and severity related to the hazards in an aluminum plate manufacturing plant are weighted by using Fuzzy Analytic Hierarchy Process (FAHP), then the orders of priority of 23 various hazard groups are determined by using Fuzzy TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method. As a follow-up study of the case application, the proposed risk assessment methodology is applied for hazard types in each department of the plant. Depending on the hazard control hierarchy, control measures are overtaken for the hazards that are placed at first of intra-department rankings. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: OHS risk assessment; DMRA technique; Fuzzy AHP; Fuzzy TOPSIS; Aluminum industry; METHODOLOGIES; MANAGEMENT; FRAMEWORK; HEALTH; TOPSIS; Engineering